OPTIMIZING THE STATE OF THE IMMUNE SYSTEM, MODERN DIAGNOSIS AND TREATMENT IN CHILDREN WITH A BACKGROUND OF HYPERSENSITIVITY TO DRUGS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Pediatric drug hypersensitivity is a rapidly evolving field. The purpose of this paper is to review the current state of pediatric drug hypersensitivity and highlight new developments in diagnosis and management.Research results: This paper will discuss the safety and use of risk stratification to proceed directly to oral challenge without prior skin testing for β-lactam reactions. We review unique aspects of pediatric drug challenges and desensitizations. It is important to accurately diagnose pediatric drug hypersensitivity reactions through a detailed history, physical examination, and available diagnostic testing. Understanding of the underlying mechanism leads to appropriate classification which is necessary to direct management. The decision to perform drug challenge, desensitization, or recommend avoidance of a medication can have a significant impact on a patient's treatment. Utilization of weight-based dose and infusion rate adjustments for current drug challenge and desensitization protocols optimize success.